Spiritual Interrogations : Culture, Gender, and Community in Early African American Women's Writing. - Bassard, Katherine Clay (Princeton University Press, 2001)
The late eighteenth century witnessed an influx of black women to the slave-trading ports of the American Northeast. The formation of an early African American community, bound together by shared experiences and spiritual values, owed much to these women's voices. The significance of their writings would be profound for all African Americans' sense of their own identity as a people. Katherine Clay Bassard's book is the first detailed account of pre-Emancipation writings from the period of 1760 to 1863, in light of a developing African American religious culture and emerging free black communiti.